Evaluasi Keandalan Infrastruktur Cloud Computing Di Politeknik Belitung Untuk Mendukung Layanan Kampus Digital - Dion Anugrah; Rizki Ananda; Eka Indah Wahyuni (Journal Of Informatics And Busisnes, 2025)
This study evaluates the reliability of cloud computing infrastructure at Belitung Polytechnic in supporting digital campus services. The evaluation was carried out by analyzing aspects of performance, security, and scalability of the cloud-based system used. The methods applied include measuring uptime, system response, and data security against cyber threats. The results of the study indicate that the cloud computing infrastructure at Belitung Polytechnic has a fairly high level of reliability, but there are still several obstacles related to latency and security that need to be improved. Recommendations for improvement are focused on optimizing the network, improving data encryption, and implementing a stricter monitoring system. With these improvements, it is hoped that digital campus services can run more efficiently and safely, supporting academic needs and campus operations optimally.